High-strength steel sheet and method for producing same
By optimizing the composition and heat treatment process of the steel plate, the shortcomings in tensile strength and bending properties of the high-strength steel plate are solved, and the flatness and processing and embrittlement resistance of the plate width direction are improved. It is suitable for automotive parts and improves the Fuel efficiency and industrial value.
Patent Information
- Application Number
- CN202380027255.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-25
- Filing Date
- 2023-01-30
- Publication Date
- 2024-12-24
AI Technical Summary
While improving tensile strength and bending properties, existing high-strength steel plates are difficult to take into account the flatness and machining and brittle resistance in the width direction of the existing high-strength steel plates, resulting in poor product dimensional accuracy and processing performance.
The martensite amount is set to 80% or more, the total of ferrite and bainite ferrite in the steel plate is set to 10% or less, and the residual austenite amount is set to 3% or more and 15% or more. The slat bundle with a maximum occupancy rate in the original austenite grain is less than 70%. Combined with specific heat treatment and cooling conditions, an optimized component composition and manufacturing method are formulated.
It has achieved high-strength steel plate with a TS of 1180MPa or above, with excellent bending, flatness in the plate width direction and processing embrittlement resistance. It is suitable for automotive structural components, improving body lightweight and fuel efficiency.
Smart Images

Figure CN119183479A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a high-strength steel sheet having excellent tensile strength, bendability, flatness in the sheet width direction, and resistance to work embrittlement, and a method for producing the same. The high-strength steel sheet of the present invention can be suitably used as a structural member such as an automobile component. Background Art
[0002] In order to reduce CO2 by reducing vehicle weight 2 To reduce emissions and improve collision resistance by reducing the weight of the vehicle body, the strength of thin steel sheets for automobiles is being increased, and new legal restrictions are also being introduced. Therefore, in order to increase the strength of the vehicle body, the use of high-strength steel sheets with a tensile strength (TS) of 1180MPa or above is increasing in the main structural parts of the vehicle.
[0003] High-strength steel sheets used in automobiles are required to have excellent bendability. For example, in parts such as bumpers having a portion bent by roll forming, it is preferred to use a steel sheet with excellent bendability from the viewpoint of formability.
[0004] In addition, high-strength steel sheets used in automobiles require excellent resistance to work embrittlement from the perspective of component performance. For example, in frame components such as automobile bumpers, it is preferred to use high-strength steel sheets with excellent resistance to work embrittlement that will not become brittle due to press forming.
[0005] In addition, high-strength steel sheets used in automobiles are also required to have excellent flatness. Patent Document 1 states that the warping of steel sheets has an adverse effect on operational failures in forming lines and the dimensional accuracy of products. The present inventors have repeatedly conducted in-depth studies and found that the dimensional accuracy of products is not only affected by the warping of steel sheets, but also by the flatness in the width direction of the sheet evaluated by steepness. For example, in order to achieve excellent dimensional accuracy, the steepness in the width direction is preferably 0.02 or less.
[0006] In response to these requirements, for example, Patent Document 2 provides a high-strength steel sheet having a tensile strength of 1100 MPa or more and excellent in YR, surface properties and weldability, and a method for manufacturing the same. However, the technology described in Patent Document 2 does not take into account the flatness in the sheet width direction and the work embrittlement resistance.
[0007] Patent Document 3 provides a hot-dip galvanized steel sheet having excellent press formability and low-temperature toughness and having a tensile strength of 980 MPa or more and a method for manufacturing the same. However, the technology described in Patent Document 3 can improve the embrittlement of the steel sheet caused by temperature reduction, but does not consider the embrittlement of the steel sheet caused by processing. Nor does it consider the bendability and flatness in the width direction of the sheet.
[0008] Patent Document 4 provides a high-strength steel sheet having a tensile strength of 1320 MPa or more and excellent workability and bendability, and a method for producing the same. However, the technology described in Patent Document 4 does not take into account flatness in the sheet width direction and resistance to work embrittlement.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent No. 4947176
[0012] Patent Document 2: Japanese Patent No. 6525114
[0013] Patent Document 3: Japanese Patent No. 6777272
[0014] Patent Document 4: Japanese Patent No. 6338025
[0015] Non-patent literature
[0016] Non-patent document 1: Intelligent Processing Magazine, 2013, Vol. 2, No. 3, p. 110-118 Summary of the invention
[0017] Problems to be solved by the invention
[0018] The present invention has been developed in view of the above circumstances, and an object of the present invention is to provide a high-strength steel sheet having a TS of 1180 MPa or more and excellent in bendability, flatness in the sheet width direction, and resistance to work embrittlement, and a method for producing the same.
[0019] Methods used to solve problems
[0020] The present inventors have conducted intensive studies to achieve the above-mentioned objects and have found the following findings.
[0021] (1) By setting the amount of martensite to 80% or more in terms of area fraction and setting the total amount of ferrite and bainitic ferrite to 10% or less in terms of area fraction, a TS of 1180 MPa or more can be achieved.
[0022] (2) By setting the amount of retained austenite to 3% or more in volume fraction, excellent bendability can be achieved.
[0023] (3) By setting the average value of the occupancy of the lath bundles having the largest occupancy in the prior austenite grains to 70% or less in terms of area fraction, it is possible to achieve excellent flatness in the sheet width direction.
[0024] (4) Excellent resistance to work embrittlement can be achieved by setting the amount of retained austenite to 15% or less in volume fraction, setting the average occupancy of lath bundles with the maximum occupancy in the original austenite grains to 70% or less in area fraction, and setting the average grain size of the original austenite to 20 μm or less.
[0025] The present invention has been completed based on the above findings. That is, the gist of the present invention is as follows.
[0026] [1] A high-strength steel sheet comprising, in mass%, 0.030% to 0.500% C, 0.50% to 2.50% Si, 1.50% to 5.00% Mn, 0.100% to 0.100% P, 0.0200% to 0.0200% S, 1.000% to 1.000% Al, 0.0100% to 0.0100% N and 0.0100% to 0.0100% O, with the remainder being Fe and inevitable impurities, at the 1 / 4 position of the plate thickness, the amount of martensite is more than 80% by area fraction, the amount of retained austenite is more than 3% and less than 15% by volume fraction, the total amount of ferrite and bainitic ferrite is less than 10% by area fraction, the average grain size of the original austenite is less than 20μm, and the average occupancy of the lath bundles with the maximum occupancy in the original austenite grains is less than 70% by area fraction.
[0027] [2] The high-strength steel sheet according to [1], wherein the above-mentioned chemical composition further contains, in mass %, at least one element selected from the group consisting of Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Co: 0.010% or less, Ni: 1.00% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, and Bi: 0.200% or less.
[0028] [3] The high-strength steel sheet according to [1] or [2], wherein the steel sheet has a plating layer on the surface.
[0029] [4] A method for producing a high-strength steel sheet according to [1] or [2], wherein a cold-rolled sheet produced by hot-rolling, pickling and cold-rolling a steel having the above-mentioned composition is annealed by heating at an annealing temperature of 750°C to 950°C and a holding time of 10 seconds to 1000 seconds, wherein during the annealing, the sheet is bent and bent back by a roller having a radius of 800 mm or less for a total of 1 to 15 times, and the sheet is cooled at an average cooling rate of 20°C / s or more in a temperature range of 700°C to 600°C and an average cooling rate of 20°C / s or more in a temperature range of 499°C to Ms. In the temperature range of 99°C to Ms, bending and bending recovery are performed by a roller with a radius of 800 mm or less, the total number of times is 1 or more and 15 or less, and cooling is performed under the condition that the average cooling rate in the temperature range of Ms to the cooling stop temperature Ta is 150°C / s or less, the tension applied to the steel sheet in the temperature range of Ms to the cooling stop temperature Ta is set to 5 MPa or more and 100 MPa or less, the cooling stop temperature Ta is 100°C or more and (Ms-80°C) or less, wherein Ms is the martensitic transformation start temperature (°C) specified by the formula (1), and tempering is performed under the conditions that the tempering temperature is Ta or more and 450°C or less and the holding time at the tempering temperature is 10 seconds or more and 1000 seconds or less.
[0030] Ms=519-474×[%C]-30.4×[%Mn]-12.1×[%Cr]-7.5×[%Mo]-17.7×[%Ni]…(1)
[0031] Here, [%C], [%Mn], [%Cr], [%Mo], and [%Ni] represent the content (mass %) of C, Mn, Cr, Mo, and Ni, respectively, and when not contained, it is set to 0.
[0032] [5] The method for producing a high-strength steel sheet according to [4], wherein a plating treatment is performed.
[0033] Effects of the Invention
[0034] According to the present invention, a high-strength steel sheet having a TS of 1180 MPa or more and excellent bendability, flatness in the plate width direction, and resistance to work embrittlement can be obtained. In addition, by applying the high-strength steel sheet of the present invention to, for example, automotive structural members, it is possible to improve fuel efficiency by reducing the weight of the vehicle body. Therefore, the industrial utilization value is extremely high. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1It is a diagram showing the structure of the lath bundle having the maximum occupancy in the prior austenite grains according to the present invention and the calculation method of the occupancy of the lath bundle.
[0036] Figure 2 This is a diagram showing the concept of the steepness λ in the width direction of the steel plate of the present invention and a calculation method thereof. DETAILED DESCRIPTION
[0037] Hereinafter, embodiments of the present invention will be described.
[0038] First, the appropriate range of the chemical composition of the high-strength steel sheet and the reasons for its limitation are described. It should be noted that in the following description, "%" indicating the content of the component elements of the steel means "mass %" unless otherwise specified.
[0039] [C: 0.030% or more and 0.500% or less]
[0040] C is one of the important basic components of steel, and is an important element that affects the total amount of martensite, ferrite and bainitic ferrite in the present invention. When the C content is less than 0.030%, the martensite amount decreases, the total amount of ferrite and bainitic ferrite increases, and it is difficult to achieve a TS of more than 1180MPa. On the other hand, when the C content is greater than 0.500%, the martensite becomes brittle and the work embrittlement resistance is reduced. Therefore, the C content is set to be greater than 0.030% and less than 0.500%. The lower limit of the C content is preferably set to be greater than 0.050%. The upper limit of the C content is preferably set to be less than 0.400%. The lower limit of the C content is more preferably set to be greater than 0.100%. The upper limit of the C content is more preferably set to be less than 0.350%.
[0041] [Si: 0.50% or more and 2.50% or less]
[0042] Si is one of the important basic components of steel and is an important element that affects TS and the amount of retained austenite. When the content of Si is less than 0.50%, the strength of martensite decreases, so it is difficult to achieve a TS of more than 1180MPa. On the other hand, when the content of Si is greater than 2.50%, the retained austenite increases excessively and the resistance to work embrittlement decreases. Therefore, the content of Si is set to more than 0.50% and less than 2.50%. The lower limit of the content of Si is preferably set to more than 0.55%. The upper limit of the content of Si is preferably set to less than 2.00%. The lower limit of the content of Si is more preferably set to more than 0.60%. The upper limit of the content of Si is more preferably set to less than 1.80%.
[0043] [Mn: 1.50% or more and 5.00% or less]
[0044] Mn is one of the important basic components of steel and is an important element that affects the total amount of martensite, ferrite and bainitic ferrite. When the content of Mn is less than 1.50%, the amount of martensite decreases, the total amount of ferrite and bainitic ferrite increases, and it is difficult to achieve a TS of more than 1180MPa. On the other hand, when the content of Mn is greater than 5.00%, martensite becomes brittle and the resistance to work embrittlement decreases. Therefore, the content of Mn is set to more than 1.50% and less than 5.00%. The lower limit of the content of Mn is preferably set to more than 2.00%. The upper limit of the content of Mn is preferably set to less than 4.50%. The lower limit of the content of Mn is more preferably set to more than 2.20%. The upper limit of the content of Mn is more preferably set to less than 4.00%.
[0045] [P: 0.100% or less]
[0046] P segregates at the original austenite grain boundary and makes the grain boundary embrittled, thereby reducing the ultimate deformation capacity of the steel plate, and thus reducing the processing embrittlement resistance. Therefore, the P content needs to be set to 0.100% or less. It should be noted that the lower limit of the P content is not particularly specified, but since P is a solid solution strengthening element, it can increase the strength of the steel plate, so it is preferably set to 0.001% or more. Therefore, the P content is set to 0.100% or less. The lower limit of the P content is preferably set to 0.001% or more. The upper limit of the P content is preferably set to 0.070% or less.
[0047] [S: 0.0200% or less]
[0048] S exists in the form of sulfide, which reduces the ultimate deformation capacity of the steel plate, thereby reducing the resistance to processing embrittlement. Therefore, the S content needs to be set to 0.0200% or less. It should be noted that the lower limit of the S content is not particularly specified, but considering the limitations of production technology, it is preferably set to 0.0001% or more. Therefore, the S content is set to 0.0200% or less. The lower limit of the S content is preferably set to 0.0001% or more. The upper limit of the S content is preferably set to 0.0050% or less.
[0049] [Al: 1.000% or less]
[0050] Al exists in the form of oxides, which reduces the ultimate deformation capacity of the steel sheet, thereby reducing the resistance to processing embrittlement. Therefore, the Al content needs to be set to 1.000% or less. It should be noted that the lower limit of the Al content is not particularly specified, but from the perspective of suppressing the formation of carbides in continuous annealing and promoting the formation of retained austenite, the Al content is preferably set to 0.001% or more. Therefore, the Al content is set to 1.000% or less. The lower limit of the Al content is preferably set to 0.001% or more. The upper limit of the Al content is preferably set to 0.500% or less.
[0051] [N: 0.0100% or less]
[0052] N exists in the form of nitrides, which reduces the ultimate deformation capacity of the steel plate, thereby reducing the resistance to processing embrittlement. Therefore, the N content needs to be set to 0.0100% or less. It should be noted that there is no special lower limit for the N content, but considering the limitations of production technology, the N content is preferably set to 0.0001% or more. Therefore, the N content is set to 0.0100% or less. The lower limit of the N content is preferably set to 0.0001% or more. The upper limit of the N content is preferably set to 0.0050% or less.
[0053] [O: 0.0100% or less]
[0054] O exists in the form of oxides, which reduces the ultimate deformation capacity of the steel plate, thereby reducing the resistance to processing embrittlement. Therefore, the content of O needs to be set to 0.0100% or less. It should be noted that there is no special lower limit for the content of O, but considering the limitations of production technology, the content of O is preferably set to 0.0001% or more. Therefore, the content of O is set to 0.0100% or less. The lower limit of the content of O is preferably set to 0.0001% or more. The upper limit of the content of O is preferably set to 0.0050% or less.
[0055] The high-strength steel sheet according to one embodiment of the present invention has a composition containing the above-mentioned components and the balance containing Fe and inevitable impurities. Here, as inevitable impurities, Zn, Pb, As, Ge, Sr and Cs can be listed. The total amount of these impurities is allowed to be 0.100% or less.
[0056] The high-strength steel sheet of the present invention may contain, in addition to the above-mentioned component composition, at least one element selected from the group consisting of Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Ni: 1.00% or less, Co: 0.010% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, and Bi: 0.200% or less, alone or in combination.
[0057] When Ti, Nb and V are respectively less than 0.200%, coarse precipitates and inclusions will not be generated in large quantities, and the ultimate deformation capacity of the steel sheet will not be reduced, so the processing embrittlement resistance will not be reduced. Therefore, the contents of Ti, Nb and V are preferably set to less than 0.200%. It should be noted that the lower limits of the contents of Ti, Nb and V are not particularly specified. During hot rolling or continuous annealing, the strength of the steel sheet is increased by forming fine carbides, nitrides or carbonitrides, so the contents of Ti, Nb and V are more preferably set to more than 0.001%. Therefore, in the case of containing Ti, Nb and V, their contents are respectively set to less than 0.200%. The lower limit in the case of containing Ti, Nb and V is more preferably set to more than 0.001%. The upper limit in the case of containing Ti, Nb and V is further preferably set to less than 0.100%.
[0058] When Ta and W are respectively less than 0.10%, coarse precipitates and inclusions will not be generated in large quantities, and the ultimate deformation capacity of the steel plate will not be reduced, so the work embrittlement resistance characteristics will not be reduced. Therefore, the contents of Ta and W are preferably set to less than 0.10%, respectively. It should be noted that the lower limits of the contents of Ta and W are not particularly specified. During hot rolling or continuous annealing, the strength of the steel plate is increased by forming fine carbides, nitrides or carbonitrides, so the contents of Ta and W are more preferably set to more than 0.01%. Therefore, in the case of containing Ta and W, their contents are respectively set to less than 0.10%. The lower limit in the case of containing Ta and W is more preferably set to more than 0.01%. The upper limit in the case of containing Ta and W is further preferably set to less than 0.08%.
[0059] When B is below 0.0100%, cracks will not be generated inside the steel plate during casting or hot rolling, and the ultimate deformation capacity of the steel plate will not be reduced, so the processing embrittlement resistance will not be reduced. Therefore, the content of B is preferably set to below 0.0100%. It should be noted that the lower limit of the content of B is not particularly specified, but since it is an element that segregates at the austenite grain boundary and improves hardenability during annealing, the content of B is more preferably set to more than 0.0003%. Therefore, in the case of containing B, its content is set to less than 0.0100%. The lower limit in the case of containing B is more preferably set to more than 0.0003%. The upper limit in the case of containing B is further preferably set to less than 0.0080%.
[0060] When Cr, Mo and Ni are respectively less than 1.00%, coarse precipitates and inclusions do not increase, and the ultimate deformation capacity of the steel plate will not be reduced, so the processing embrittlement resistance characteristics will not be reduced. Therefore, the contents of Cr, Mo and Ni are preferably set to less than 1.00%, respectively. It should be noted that the lower limits of the contents of Cr, Mo and Ni are not particularly specified, but since they are elements that improve hardenability, the contents of Cr, Mo and Ni are more preferably set to more than 0.01%, respectively. Therefore, in the case of containing Cr, Mo and Ni, their contents are respectively set to less than 1.00%. The lower limit in the case of containing Cr, Mo and Ni is more preferably set to more than 0.01%. The upper limit in the case of containing Cr, Mo and Ni is further preferably set to less than 0.80%.
[0061] When Co is below 0.010%, coarse precipitates and inclusions do not increase, and the ultimate deformation capacity of the steel plate will not be reduced, so the processing embrittlement resistance characteristic will not be reduced. Therefore, the content of Co is preferably set to below 0.010%. It should be noted that the lower limit of the content of Co is not particularly specified, but since it is an element that improves hardenability, the content of Co is more preferably set to above 0.001%. Therefore, in the case of containing Co, its content is set to below 0.010%. The lower limit in the case of containing Co is more preferably set to above 0.001%. The upper limit in the case of containing Co is further preferably set to below 0.008%.
[0062] When Cu is below 1.00%, coarse precipitates and inclusions do not increase, and the ultimate deformation capacity of the steel plate will not be reduced, so the processing embrittlement resistance characteristic will not be reduced. Therefore, the content of Cu is preferably set to below 1.00%. It should be noted that the lower limit of the content of Cu is not particularly specified, but since it is an element that improves hardenability, the content of Cu is preferably set to more than 0.01%. Therefore, in the case of containing Cu, its content is set to less than 1.00%. The lower limit in the case of containing Cu is more preferably set to more than 0.01%. The upper limit in the case of containing Cu is further preferably set to less than 0.80%.
[0063] When Sn is below 0.200%, cracks will not be generated inside the steel plate during casting or hot rolling, and the ultimate deformation capacity of the steel plate will not be reduced, so the processing embrittlement resistance characteristic will not be reduced. Therefore, the content of Sn is preferably set to below 0.200%. It should be noted that the lower limit of the content of Sn is not particularly specified, but since Sn is an element that improves hardenability (generally an element that improves corrosion resistance), the content of Sn is more preferably set to more than 0.001%. Therefore, in the case of containing Sn, its content is set to less than 0.200%. The lower limit in the case of containing Sn is more preferably set to more than 0.001%. The upper limit in the case of containing Sn is further preferably set to less than 0.100%.
[0064] When Sb is less than 0.200%, coarse precipitates and inclusions do not increase, and the ultimate deformation capacity of the steel plate will not be reduced, so the processing embrittlement resistance will not be reduced. Therefore, the Sb content is preferably set to less than 0.200%. It should be noted that the lower limit of the Sb content is not particularly specified, but since it is an element that can control the softening thickness of the surface layer and can adjust the strength, the Sb content is more preferably set to more than 0.001%. Therefore, in the case of containing Sb, its content is set to less than 0.200%. The lower limit in the case of containing Sb is more preferably set to more than 0.001%. The upper limit in the case of containing Sb is further preferably set to less than 0.100%.
[0065] When Ca, Mg and REM are respectively less than 0.0100%, coarse precipitates and inclusions do not increase, and the ultimate deformation capacity of the steel sheet will not be reduced, so the work embrittlement resistance characteristics will not be reduced. Therefore, the content of Ca, Mg and REM is preferably set to 0.0100% or less. It should be noted that the lower limit of the content of Ca, Mg and REM is not particularly specified, but since they are elements that make the shape of nitrides and sulfides spherical and improve the ultimate deformation capacity of the steel sheet, the content of Ca, Mg and REM is more preferably set to 0.0005% or more. Therefore, in the case of containing Ca, Mg and REM, their contents are respectively set to 0.0100% or less. The lower limit in the case of containing Ca, Mg and REM is more preferably set to 0.0005% or more. The upper limit in the case of containing Ca, Mg and REM is further preferably set to 0.0050% or less.
[0066] When Zr and Te are respectively less than 0.100%, coarse precipitates and inclusions do not increase, and the ultimate deformation capacity of the steel plate will not be reduced, so the processing embrittlement resistance characteristics will not be reduced. Therefore, the content of Zr and Te is preferably set to 0.100% or less. It should be noted that the lower limit of the content of Zr and Te is not particularly specified, but since it is an element that makes the shape of nitrides and sulfides spherical and improves the ultimate deformation capacity of the steel plate, the content of Zr and Te is more preferably set to 0.001% or more. Therefore, in the case of containing Zr and Te, their contents are respectively set to 0.100% or less. The lower limit in the case of containing Zr and Te is more preferably set to 0.001% or more. The upper limit in the case of containing Zr and Te is further preferably set to 0.080% or less.
[0067] When Hf is less than 0.10%, coarse precipitates and inclusions do not increase, and the ultimate deformation capacity of the steel plate will not be reduced, so the resistance to processing embrittlement will not be reduced. Therefore, the content of Hf is preferably set to 0.10% or less. It should be noted that the lower limit of the content of Hf is not particularly specified, but since it is an element that makes the shape of nitrides and sulfides spherical and improves the ultimate deformation capacity of the steel plate, the content of Hf is more preferably set to 0.01% or more. Therefore, in the case of containing Hf, its content is set to 0.10% or less. The lower limit in the case of containing Hf is more preferably set to 0.01% or more. The upper limit in the case of containing Hf is further preferably set to 0.08% or less.
[0068] When Bi is less than 0.200%, coarse precipitates and inclusions do not increase, and the ultimate deformation capacity of the steel plate will not be reduced, so the resistance to processing embrittlement will not be reduced. Therefore, the content of Bi is preferably set to less than 0.200%. It should be noted that the lower limit of the content of Bi is not particularly specified, but since it is an element that reduces segregation, the content of Bi is more preferably set to more than 0.001%. Therefore, in the case of containing Bi, its content is set to less than 0.200%. The lower limit in the case of containing Bi is more preferably set to more than 0.001%. The upper limit in the case of containing Bi is further preferably set to less than 0.100%.
[0069] It should be noted that, with respect to the above-mentioned Ti, Nb, V, Ta, W, B, Cr, Mo, Ni, Co, Cu, Sn, Sb, Ca, Mg, REM, Zr, Te, Hf and Bi, when the content of each is less than the preferred lower limit, the effect of the present invention will not be impaired, and therefore they are contained as unavoidable impurities.
[0070] Next, the steel structure of the high-strength steel sheet of the present invention will be described.
[0071] [The area fraction of martensite is 80% or more]
[0072] It is an extremely important invention constituent element in the present invention. By setting the amount of martensite to 80% or more in terms of area fraction, a TS of 1180 MPa or more can be achieved. Therefore, the martensite is set to 80% or more in terms of area fraction. Preferably, it is 82% or more. More preferably, it is 84% or more.
[0073] [The amount of retained austenite is 3% or more and 15% or less in volume fraction]
[0074] It is an extremely important invention constituent element in the present invention. When the amount of retained austenite is less than 3% by volume fraction, the crack suppression effect during bending processing generated by the retained austenite cannot be obtained, and it is difficult to achieve excellent bendability. In addition, when the amount of retained austenite is greater than 15%, since the retained austenite is excessively transformed into hard martensite when processing is applied, the ultimate deformation capacity of the steel plate is reduced, and it is difficult to obtain excellent resistance to processing embrittlement. Therefore, the amount of retained austenite is set to more than 3% and less than 15%. The lower limit of the amount of retained austenite is preferably set to more than 5%. The upper limit of the amount of retained austenite is preferably set to less than 14%. The lower limit of the amount of retained austenite is more preferably set to more than 7%. The upper limit of the amount of retained austenite is more preferably set to less than 13%.
[0075] Here, the method for measuring retained austenite is as follows. Retained austenite is obtained by grinding a steel plate from a 1 / 4 portion of the plate thickness to a surface of 0.1 mm, then further grinding 0.1 mm by chemical grinding, and measuring the integrated intensity ratios of the diffraction peaks of the {200}, {220}, and {311} planes of fcc iron and the {200}, {211}, and {220} planes of bcc iron using an X-ray diffractometer using CoKα rays, and averaging the obtained 9 integrated intensity ratios to obtain retained austenite.
[0076] [The total amount of ferrite and bainitic ferrite is 10% or less in terms of area fraction]
[0077] It is an extremely important inventive constituent element in the present invention. When the total amount of ferrite and bainitic ferrite is greater than 10%, it is difficult to achieve a TS of 1180 MPa or more. Therefore, the total amount of ferrite and bainitic ferrite is set to 10% or less. It is preferably set to 8% or less. It is more preferably set to 5% or less. It should be noted that the lower limit of the total amount of ferrite and bainitic ferrite is not particularly limited. It can also be 0%.
[0078] Here, the method for determining the total amount of ferrite and bainitic ferrite is as follows. After grinding the L section of the steel plate, it is corroded with a 3 volume % nitric acid ethanol solution, and 10 fields of view are observed at a magnification of 2000 times for 1 / 4 of the plate thickness (a position equivalent to 1 / 4 of the plate thickness in the depth direction from the surface of the steel plate). It should be noted that in the above-mentioned organizational image, ferrite and bainitic ferrite are organizations with concave parts and flat inside the organization, and are organizations without carbides inside. The total amount of ferrite and bainitic ferrite can be calculated from the average value of these values.
[0079] The method for determining the amount of martensite is as follows. The amount of martensite can be determined by measuring the amount of retained austenite, the amount of ferrite, and the amount of bainitic ferrite based on the above method, and deducting their total from 100%. Therefore, the amount of martensite in the present invention refers to the amount of both quenched martensite and tempered martensite. It should be noted that in the deduction, since the volume ratio of the amount of retained austenite ≈ the area ratio, it is deducted from 100% together with the amount of ferrite and the amount of bainitic ferrite represented by the area ratio.
[0080] [Average grain size of prior austenite is 20 μm or less]
[0081] It is an extremely important inventive constituent element in the present invention. By reducing the average grain size of the original austenite, the propagation of cracks can be suppressed, thereby improving the work embrittlement resistance of the steel plate. In order to obtain such an effect, it is necessary to set the average grain size of the original austenite to less than 20μm. It should be noted that there is no special lower limit for the average grain size of the original austenite, but considering the limitations of production technology, it is preferably above 2μm. Therefore, the average grain size of the original austenite is set to less than 20μm. It is preferably set to more than 2μm. It is preferably set to less than 15μm. It is more preferably set to more than 3μm. It is more preferably set to less than 10μm.
[0082] Here, the method for measuring the average grain size of the original austenite is as follows. After grinding the L section of the steel plate, etching is performed with a mixed solution of picric acid and ferric chloride to make the original austenite grain boundary appear, and then 3 to 10 fields of view are photographed at a magnification of 400 times for 1 / 4 of the plate thickness (a position equivalent to 1 / 4 of the plate thickness in the depth direction from the surface of the steel plate). For the obtained image data, 20 straight lines of 10 vertical × 10 horizontal are drawn at equal intervals and obtained by the cutting method.
[0083] [The average occupancy of the lath bundle having the largest occupancy in the prior austenite grains is 70% or less in terms of area fraction]
[0084] It is an extremely important inventive element in the present invention. The occupancy rate of the lath bundle with the largest occupancy rate in the original austenite grain affects the flatness in the width direction of the plate and the work embrittlement resistance. The lath bundle with the largest occupancy rate in the original austenite grain refers to, for example Figure 1 As shown, there are at most four regions in the prior austenite grains called lath bundles having the same crystal habit planes during the phase transformation, and the lath bundle has the largest occupancy among them.
[0085] The occupancy rate of one lath bundle in the prior austenite grain is obtained by dividing the area of a specified lath bundle by the entire area of the prior austenite grain.
[0086] The inventors of the present invention have repeatedly conducted in-depth studies and found that by reducing the occupancy of lath bundles with the largest occupancy rate within the original austenite grains, the strain between the lath bundles is relaxed and the flatness in the plate width direction is improved. It is also found that by reducing the occupancy rate of lath bundles with the largest occupancy rate within the original austenite grains, the structure is refined, the propagation of cracks can be suppressed, and thus the work embrittlement resistance of the steel plate is improved. Therefore, the average value of the occupancy rate of lath bundles with the largest occupancy rate within the original austenite grains is set to less than 70%. It is preferably set to less than 60%. It should be noted that the lower limit of the average value of the occupancy rate of lath bundles with the largest occupancy rate within the original austenite grains is not specifically limited. The types of lath bundles are up to 4, and when 4 lath bundles are equally present, the occupancy rate of lath bundles with the largest occupancy rate within the original austenite grains is 25%. Therefore, the lower limit of the average value of the occupancy of the lath bundles having the maximum occupancy in the prior austenite grains is preferably 25% or more, but is not necessarily limited thereto.
[0087] Here, the method for determining the average occupancy of the lath bundle with the maximum occupancy in the original austenite grain is as follows. First, a test piece for tissue observation is cut from a cold-rolled steel plate. Then, the cut test piece is polished by colloidal silica vibration polishing in a manner that the rolling direction section (L section) is used as the observation surface. Make the observation surface a mirror surface. Next, electron backscatter diffraction (EBSD) measurement is performed on 1 / 4 of the plate thickness (a position equivalent to 1 / 4 of the plate thickness in the depth direction from the surface of the steel plate) to obtain local crystal orientation data. At this time, the SEM magnification is set to 1000 times, the step size is set to 0.2μm, the measurement area is set to 80μm square, and the WD is set to 15mm. The obtained local orientation data is analyzed using OIMAnalysis7 (OIM), and a color-differentiated diagram (CP mapping) is prepared according to the method described in non-patent document 1 according to the close-packed plane group (Close-packed Planegroup, CP group). In the present invention, lath bundles are defined as areas belonging to the same CP group. The area of the lath bundle with the maximum occupancy is obtained from the obtained CP map, and divided by the entire area in the original austenite grain, thereby obtaining the occupancy of the lath bundle with the maximum occupancy in the original austenite grain. This analysis is performed on more than 10 adjacent original austenite grains, and the average value is taken as the average occupancy of the lath bundle with the maximum occupancy in the original austenite grain.
[0088] Next, the production method of the present invention will be described.
[0089] In the present invention, the method for melting the steel raw material (steel slab) is not particularly limited, and any known melting method such as a converter or an electric furnace is suitable. In order to prevent macrosegregation, the steel slab is preferably produced by a continuous casting method.
[0090] In the present invention, the billet heating temperature, billet soaking holding time and coiling temperature in hot rolling are not particularly limited. As methods for hot rolling a billet, there can be cited a method of rolling the billet after heating it, a method of directly rolling the billet without heating the billet after continuous casting, a method of heating the billet after continuous casting for a short time and then rolling it, etc. The billet heating temperature, billet soaking holding time, finish rolling temperature and coiling temperature in hot rolling are not particularly limited, and the lower limit of the billet heating temperature is preferably above 1100°C. The upper limit of the billet heating temperature is preferably below 1300°C. The lower limit of the billet soaking holding time is preferably above 30 minutes. The upper limit of the billet soaking holding time is preferably below 250 minutes. The lower limit of the finish rolling temperature is preferably Ar 3 The lower limit of the coiling temperature is preferably 350°C or higher. The upper limit of the coiling temperature is preferably 650°C or lower.
[0091] The hot-rolled steel sheet manufactured in this way is pickled. Pickling can remove oxides on the surface of the steel sheet, so it is important for ensuring good chemical conversion treatment and plating quality of the high-strength steel sheet of the final product. In addition, pickling can be performed once or in multiple times. In addition, cold rolling can be performed while the pickled sheet is kept after hot rolling, or cold rolling can be performed after heat treatment.
[0092] The reduction ratio in cold rolling and the plate thickness after rolling are not particularly limited, but the lower limit of the reduction ratio is preferably 30% or more. In addition, the upper limit of the reduction ratio is preferably set to 80% or less. It should be noted that the number of rolling passes and the reduction ratio of each pass are not particularly limited, and the effect of the present invention can be obtained.
[0093] The cold rolled steel sheet obtained as described above was annealed. The annealing conditions were as follows.
[0094] [Annealing temperature is 750°C or higher and 950°C or lower]
[0095] When the annealing temperature is less than 750°C, the amount of martensite decreases, the total amount of ferrite and bainitic ferrite increases, and it is difficult to achieve a TS of 1180 MPa or more. On the other hand, when the annealing temperature is greater than 950°C, the original austenite grain size increases excessively, the original austenite grain size is greater than 20 μm, and the work embrittlement resistance is reduced. Therefore, the annealing temperature is set to be greater than 750°C and less than 950°C. The lower limit of the annealing temperature is preferably greater than 800°C. The upper limit of the annealing temperature is preferably less than 900°C.
[0096] [Annealing is performed under the condition that the holding time at the annealing temperature is 10 seconds or more and 1000 seconds or less]
[0097] When the holding time at the annealing temperature is less than 10 seconds, the amount of martensite decreases, the total amount of ferrite and bainitic ferrite increases, and it is difficult to achieve a TS of more than 1180MPa. On the other hand, when the holding time at the annealing temperature is greater than 1000 seconds, the original austenite grain size increases excessively, and the resistance to work embrittlement decreases. Therefore, the holding time at the annealing temperature is set to more than 10 seconds and less than 1000 seconds. The lower limit of the holding time at the annealing temperature is preferably more than 50 seconds. The upper limit of the holding time at the annealing temperature is preferably less than 500 seconds.
[0098] [Bending and bending recovery are performed by a roller having a radius of 800 mm or less for a total of 1 or more and 15 or less times during annealing]
[0099] The inventors of the present invention have repeatedly conducted in-depth studies and found that the bending and bending recovery of the steel sheet during annealing have an impact on the occupancy of the lath bundle with the maximum occupancy in the original austenite grains. In the case where the bending and bending recovery are not performed by a roller with a radius of 800 mm or less during annealing, the nucleation sites of the martensitic transformation are reduced. Therefore, the average occupancy of the lath bundle with the maximum occupancy in the original austenite grains is greater than 70%, the flatness in the width direction of the plate deteriorates, and the resistance to work embrittlement is reduced. On the other hand, in the case of bending and bending recovery more than 16 times using a roller with a radius of 800 mm or less during annealing, the ultimate deformation capacity of the steel sheet is reduced and the resistance to work embrittlement is reduced. Therefore, in annealing, bending and bending recovery are performed by a roller with a radius of 800 mm or less for a total of more than 1 time and less than 15 times. The radius of the preferred roller diameter is 600 mm or less. The lower limit of the number of bending and bending recovery is preferably 3 times or more in total. The upper limit of the number of bending and bending recovery is preferably 10 times or less in total. The lower limit of the radius of the roller diameter does not need to be particularly limited, but is preferably 50 mm or more.
[0100] It should be noted that bending and bending recovery refers to a process of bending in one direction using a roller by a known method and then bending in the opposite direction to recover the above bending amount. The number of bending and bending recovery is not counted as one time of bending-bending recovery, but as one time of bending and one time of bending recovery.
[0101] [The average cooling rate in the temperature range of 700°C to 600°C is 20°C / s or more]
[0102] The inventors of the present invention have repeatedly conducted in-depth studies and found that the average cooling rate in the temperature range of 700°C to 600°C has an effect on the occupancy of the lath bundles with the largest occupancy in the original austenite grains. When the average cooling rate in the temperature range of 700°C to 600°C is less than 20°C / s, the influence of bending and bending recovery on the steel sheet during annealing is reduced, and the nucleation sites of the martensitic transformation are reduced. Therefore, the average occupancy of the lath bundles with the largest occupancy in the original austenite grains is greater than 70%, the flatness in the plate width direction deteriorates, and the resistance to work embrittlement is reduced. Therefore, the average cooling rate of 750°C to 600°C is set to 20°C / s or more. Preferably, it is 30°C / s or more. The upper limit does not need to be particularly limited, and is preferably 100°C / s or less.
[0103] [The average cooling rate in the temperature range of 499℃ to Ms is 20℃ / s or more]
[0104] The average cooling rate in the temperature range of 499°C to Ms has an effect on the total area fraction of the amount of ferrite and the amount of bainitic ferrite. When the average cooling rate in the temperature range of 499°C to Ms is less than 20°C / s, the total amount of ferrite and the amount of bainitic ferrite increases, making it difficult to achieve a TS of more than 1180 MPa. Therefore, the average cooling rate in the temperature range of 499°C to Ms is set to be greater than 20°C / s. Preferably, it is greater than 25°C / s. The upper limit does not need to be particularly limited, but is preferably less than 100°C / s.
[0105] It should be noted that the martensitic transformation start temperature Ms (° C.) is defined by the following formula (1).
[0106] Ms=519-474×[%C]-30.4×[%Mn]-12.1×[%Cr]-7.5×[%Mo]-17.7×[%Ni]…(1)
[0107] Here, [%C], [%Mn], [%Cr], [%Mo], and [%Ni] represent the content (mass %) of C, Mn, Cr, Mo, and Ni, respectively, and when not contained, it is set to 0.
[0108] [Bending and bending recovery are performed at least once and 15 times in total using a roller with a radius of 800 mm or less in a temperature range of 499°C to Ms]
[0109] The inventors of the present invention have repeatedly conducted in-depth studies and found that the bending and bending recovery of the steel sheet in the temperature range of 499°C to Ms has an effect on the occupancy of the lath bundle with the maximum occupancy in the original austenite grains. In the case where the bending and bending recovery are not performed by a roller with a radius of 800 mm or less in the temperature range of 499°C to Ms, the nucleation sites of martensite are reduced. Therefore, the average occupancy of the lath bundle with the maximum occupancy in the original austenite grains is greater than 70%, the flatness in the width direction of the plate deteriorates, and the resistance to work embrittlement is reduced. On the other hand, in the case of bending and bending recovery more than 16 times by a roller with a radius of 800 mm or less in the temperature range of 499°C to Ms, the ultimate deformation capacity of the steel sheet is reduced, and the resistance to work embrittlement is reduced. Therefore, bending and bending recovery are performed by a roller with a radius of 800 mm or less in the temperature range of 499°C to Ms for a total of more than 1 time and less than 15 times. The radius of the preferred roller diameter is 600 mm or less. The lower limit of the number of bending and bending recovery is preferably 3 times or more in total. The lower limit of the number of times of bending and bending recovery is preferably 10 or less in total. The lower limit of the radius of the roller diameter does not need to be particularly limited, but is preferably 50 mm or more.
[0110] [The average cooling rate in the temperature range from Ms to cooling stop temperature Ta is 150°C / s or less]
[0111] The inventors of the present invention have repeatedly conducted in-depth research and found that the average cooling rate in the temperature range of Ms to the cooling stop temperature Ta has an impact on the occupancy of the lath bundle with the largest occupancy in the original austenite grain. When the average cooling rate in the temperature range of Ms to the cooling stop temperature Ta is greater than 150°C / s, since the martensitic phase transformation rate is fast and one lath bundle is easy to grow, the average occupancy of the lath bundle with the largest occupancy in the original austenite grain is greater than 70%, the flatness in the plate width direction deteriorates, and the resistance to processing embrittlement is reduced. Therefore, the average cooling rate in the temperature range of Ms to the cooling stop temperature Ta is set to less than 150°C / s. Preferably, it is less than 120°C / s. The lower limit does not need to be specifically limited, and is preferably greater than 5°C / s.
[0112] [The tension applied to the steel sheet in the temperature range from Ms to the cooling stop temperature Ta is 5 MPa or more and 100 MPa or less]
[0113] The inventors of the present invention have repeatedly conducted in-depth studies and found that the tension applied to the steel sheet in the temperature range of Ms to the cooling stop temperature Ta has an effect on the occupancy of the lath bundle with the maximum occupancy in the original austenite grains. When the tension applied to the steel sheet in the temperature range of Ms to the cooling stop temperature Ta is less than 5 MPa, the nucleation sites of martensite are reduced. Therefore, the average occupancy of the lath bundle with the maximum occupancy in the original austenite grains is greater than 70%, the flatness in the plate width direction deteriorates, and the work embrittlement resistance is reduced. On the other hand, when the tension applied to the steel sheet in the temperature range of Ms to the cooling stop temperature Ta is greater than 100 MPa, the ultimate deformation capacity of the steel sheet is reduced, and the work embrittlement resistance is reduced. Therefore, the tension applied to the steel sheet in the temperature range of Ms to the cooling stop temperature Ta is set to be greater than 5 MPa and less than 100 MPa. The lower limit of the tension applied to the steel sheet in the temperature range of Ms to the cooling stop temperature Ta is preferably greater than 6 MPa. The upper limit of the tension applied to the steel sheet in the temperature range of Ms to the cooling stop temperature Ta is preferably less than 50 MPa. In addition, the application of tension is performed by a well-known method. As an example, a method of applying tension by controlling the roll speed of the roll in the furnace can be performed.
[0114] It should be noted that the bending and bending recovery steps increase the number of nucleation sites that are the starting sites of martensitic transformation, but on the other hand, the tension-imparting step has a different effect in promoting martensitic transformation itself.
[0115] [Cooling stop temperature Ta is 100°C or higher and (Ms-80°C) or lower]
[0116] When the cooling stop temperature Ta is less than 100°C, the amount of retained austenite decreases and the bendability decreases. On the other hand, when the cooling stop temperature Ta is greater than (Ms-80°C), the amount of retained austenite increases excessively, the original austenite grain size increases excessively, and the work embrittlement resistance decreases. Therefore, the cooling stop temperature Ta is set to be greater than 100°C and less than (Ms-80°C). The lower limit of the cooling stop temperature Ta is preferably greater than 120°C. The upper limit of the cooling stop temperature Ta is preferably less than (Ms-100°C).
[0117] [Tempering temperature is Ta or higher and 450°C or lower]
[0118] After stopping cooling at the above-mentioned cooling stop temperature Ta, the steel is maintained at this temperature, or reheated and maintained at a temperature below 450°C to stabilize the retained austenite. When the tempering temperature is less than Ta, the specified retained austenite cannot be obtained, so the bendability is reduced. When the tempering temperature is greater than 450°C, the tempering of martensite is excessive, and it is difficult to achieve a TS of more than 1180 MPa. Therefore, the tempering temperature is set to be greater than Ta and less than 450°C. The lower limit of the tempering temperature is preferably greater than (Ta+10°C). The upper limit of the tempering temperature is preferably less than 420°C.
[0119] [The holding time at the tempering temperature is 10 seconds or more and 1000 seconds or less]
[0120] When the holding time at the tempering temperature is less than 10 seconds, the stabilization of austenite becomes insufficient, and the specified retained austenite cannot be obtained, so the bendability decreases. When the holding time at the tempering temperature is more than 1000 seconds, the tempering of martensite is excessively performed, and it is difficult to achieve a TS of more than 1180 MPa. Therefore, the holding time at the tempering temperature is set to be more than 10 seconds and less than 1000 seconds. The lower limit of the holding time at the tempering temperature is preferably more than 50 seconds. The upper limit of the holding time at the tempering temperature is preferably less than 800 seconds.
[0121] The cooling after tempering does not need to be particularly specified, and the material may be cooled to a desired temperature by any method. It should be noted that the desired temperature is preferably about room temperature.
[0122] The high-strength steel sheet may be processed under conditions to achieve an equivalent plastic strain of 0.10% to 5.00%, or reheated again at 100° C. to 400° C. after processing.
[0123] In addition, when a high-strength steel sheet is traded, it is usually traded after being cooled to room temperature.
[0124] The high-strength steel sheet may be plated during or after annealing.
[0125] As the plating treatment during annealing, for example, a hot-dip galvanizing treatment during or after cooling under the condition that the average cooling rate at 700°C to 600°C is 20°C / s or more after annealing, or an alloying treatment after hot-dip galvanizing can be exemplified. In addition, as the plating treatment after annealing, for example, a Zn-Ni electroplating alloy treatment or a pure Zn electroplating treatment after tempering can be exemplified. A plating layer can be formed by electroplating, and hot-dip galvanizing-aluminum-magnesium alloy can also be implemented. It should be noted that in the above-mentioned plating treatment, the case of galvanizing is mainly described, but the type of plating metal such as Zn plating and Al plating is not particularly limited. The conditions of other manufacturing methods are not particularly limited. From the perspective of productivity, the above-mentioned series of treatments such as annealing, hot-dip galvanizing, and alloying treatment of the galvanized layer are preferably performed by CGL (Continuous Galvanizing Line: Continuous Hot-dip Galvanizing Line) as a hot-dip galvanizing line. After hot-dip galvanizing, wiping can be performed to adjust the unit area weight of the plating layer. It should be noted that the plating and other conditions other than the above conditions can be carried out according to a conventional hot-dip galvanizing method.
[0126] After the annealing and plating treatment, the steel may be worked again under the condition that the equivalent plastic strain is 0.10% or more and 5.00 or less. Also, after the working, the steel may be reheated again under the condition of 100° C. or more and 400° C. or less.
[0127] Example
[0128] Steel having the composition shown in Tables 1 and 2, with the remainder consisting of Fe and inevitable impurities, is melted in a converter and made into a steel billet by a continuous casting method. Next, the obtained steel billet is heated, pickled after hot rolling, and then cold rolled, and annealed as shown in Tables 3 and 4 to obtain a high-strength cold-rolled steel sheet with a thickness of 0.6 to 2.2 mm. For bending and bending recovery during annealing, a roller with a radius of 300 mm is used, and for bending and bending recovery in the temperature range of 499°C to Ms, a roller with a radius of 300 mm is used. It should be noted that for some steel sheets, a plating treatment is performed during or after annealing to obtain a high-strength cold-rolled steel sheet.
[0129] The high-strength cold-rolled steel sheets obtained as described above were used as test steels, and tensile properties, bendability, flatness in the sheet width direction, and work embrittlement resistance were evaluated according to the following test methods.
[0130]
[0131]
[0132]
[0133]
[0134] (Organization Observation)
[0135] The total amount of martensite, the amount of retained austenite, the amount of ferrite, the amount of bainitic ferrite, and the prior austenite average grain size were determined by the above method.
[0136] (Occupancy of lath bundles with maximum occupancy in the original austenite grain)
[0137] According to the above method, the average value of the occupancy of the lath bundle having the maximum occupancy in the prior austenite grains is obtained.
[0138] (Tensile test)
[0139] In the tensile test, a JIS No. 5 test piece (point distance 50 mm, parallel part width 25 mm) was cut so that the long side of the test piece was perpendicular to the rolling direction, and the test was carried out according to JIS Z 2241. -1 The tensile test was performed under the condition of 1100 MPa / s to measure TS. It should be noted that in the present invention, a TS of 1180 MPa or more was judged as acceptable.
[0140] (Flexibility)
[0141] Regarding bendability, a 30 mm × 100 mm test piece was cut and tested according to the V-block method of JIS Z 2248 to measure the minimum bending radius R at which no cracks occur in the bending ridge. It should be noted that the bending direction is the long side direction of the test piece. The value obtained by dividing the minimum bending radius (R) by the plate thickness (t) is set to R / t. The case where R / t is less than 6.0 is judged to be excellent in bendability. Here, the presence or absence of cracks is evaluated by measuring the ridge of the bending vertex at a magnification of 40 times using a digital microscope (RH-2000: manufactured by Hiroshi Co., Ltd.).
[0142] (Flatness in the board width direction)
[0143] For various cold-rolled steel sheets obtained through the above operations, Figure 2 Specifically, a plate with a length of 500 mm (coil width × 500 mmL × plate thickness) is cut from the coil along the rolling direction, and placed on a platform with the warped end face facing upward. A contact displacement meter with a stylus moving on the measured object is used to continuously measure the height of the steel plate in the entire width direction. According to the results, Figure 2The method shown measures the steepness, which is an index indicating the flatness of the shape of the steel plate. A steel plate with a steepness greater than 0.02 is evaluated as "×", a steel plate with a steepness greater than 0.01 and less than 0.02 is evaluated as "○", a steel plate with a steepness of less than 0.01 is evaluated as "◎", and a steel plate with a steepness of less than 0.02 is judged as "excellent flatness in the plate width direction".
[0144] (Machining embrittlement resistance)
[0145] The resistance to work embrittlement is evaluated by the Charpy test. For the Charpy test piece, multiple steel plates are overlapped and fastened with bolts. After confirming that there is no gap between the steel plates, a test piece with a V-shaped notch with a depth of 2 mm is made. The number of overlapping steel plates is set so that the thickness of the test piece after stacking is closest to 10 mm. For example, in the case of a plate thickness of 1.2 mm, 8 plates are stacked and the test piece thickness is 9.6 mm. The stacked Charpy test piece is cut with the plate width direction as the long side. As an indicator of the resistance to work embrittlement, the ratio of the impact absorption energy at room temperature between the steel plate in the manufactured state (unprocessed) and the steel plate subjected to 10% rolling, vE, is measured. 0% / vE 10% . 0% / vE 10% The steel plates with a value less than 0.6 were evaluated as “×” and vE 0% / vE 10% The steel plates with vE of 0.6 or more and less than 0.7 were evaluated as "○", and vE 0% / vE 10% The steel plates with a vE of 0.7 or more were rated as “◎”. 0% / vE 10% A steel plate with a value of 0.6 or more is judged to be “excellent in resistance to work embrittlement.” It should be noted that the conditions other than those described above are in accordance with JIS Z2242:2018.
[0146] The results are summarized in Tables 5 to 7. As shown in Tables 5 to 7, in the examples of the present invention, TS was 1180 MPa or more, and the bendability, flatness in the plate width direction, and resistance to work embrittlement were excellent. On the other hand, in the comparative examples, one or more of TS, bendability, flatness in the plate width direction, or resistance to work embrittlement were poor.
[0147]
[0148]
[0149]
Claims
1. A high-strength steel plate, Its component composition is as follows: in mass %, it contains C: 0.030% to 0.500%, Si: 0.50% to 2.50%, Mn: 1.50% to 5.00%, P: 0.100% to 0.0200% to 0.0200%, Al: 1.000% to 1.000%, N: 0.0100% to 0.0100% and O: 0.0100% to 0.0100%, and the balance is Fe and unavoidable impurities. At the 1 / 4 position of the plate thickness, the amount of martensite is more than 80% by area fraction, the amount of retained austenite is more than 3% and less than 15% by volume fraction, the total amount of ferrite and bainitic ferrite is less than 10% by area fraction, the average grain size of the original austenite is less than 20 μm, and the average occupancy of the lath bundles with the maximum occupancy in the original austenite grains is less than 70% by area fraction.
2. The high-strength steel plate according to claim 1, wherein: The component composition further contains, in mass %, at least one element selected from the group consisting of Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Co: 0.010% or less, Ni: 1.00% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, and Bi: 0.200% or less.
3. The high-strength steel sheet according to claim 1 or 2, wherein: The steel plate has a coating on its surface.
4. A method for producing a high-strength steel sheet, which is the method for producing a high-strength steel sheet according to claim 1 or 2, wherein: For a cold-rolled sheet produced by hot-rolling, pickling and cold-rolling the steel having the above-mentioned chemical composition, Annealing is performed by heating under the conditions that the annealing temperature is 750° C. or higher and 950° C. or lower and the holding time at the annealing temperature is 10 seconds or higher and 1000 seconds or lower, In the annealing, the bending and bending recovery are performed by a roller with a radius of 800 mm or less for a total of 1 or more times and 15 or less times, Cooling is performed under the conditions that the average cooling rate in the temperature range of 700°C to 600°C is 20°C / s or more, and the average cooling rate in the temperature range of 499°C to Ms is 20°C / s or more, In the temperature range of 499° C. to Ms, the bending and bending recovery are performed by a roller with a radius of 800 mm or less for a total of 1 or more times and 15 or less times, Cooling is performed under the condition that the average cooling rate in the temperature range from Ms to the cooling stop temperature Ta is 150°C / s or less. The tension applied to the steel sheet in the temperature range of Ms to the cooling stop temperature Ta is set to 5 MPa or more and 100 MPa or less. The cooling stop temperature Ta is 100°C or higher and (Ms-80°C) or lower. Where Ms is the martensitic transformation starting temperature (°C) specified by equation (1), Tempering is performed under the conditions that the tempering temperature is Ta or higher and 450° C. or lower and the holding time at the tempering temperature is 10 seconds or higher and 1000 seconds or lower, Ms=519-474×[%C]-30.4×[%Mn]-12.1×[%Cr]-7.5×[%Mo]-17.7×[%Ni]…(1) Here, [%C], [%Mn], [%Cr], [%Mo], and [%Ni] represent the content (mass %) of C, Mn, Cr, Mo, and Ni, respectively, and when not contained, it is set to 0.
5. The method for producing a high-strength steel sheet according to claim 4, wherein: A plating treatment is performed.
